Towards Exascale Simulations of the ICM Dynamo with WENO-Wombat - Julius Donnert (Galaxies, 2018)
In galaxy clusters, modern radio interferometers observe non-thermal radio sources with unprecedented spatial and spectral resolution. For the first time, the new data allows to infer the structure of the intra-cluster magnetic fields on small scales via Faraday tomography. This leap forward demands new numerical models for the amplification of magnetic fields in cosmic structure formation—the cosmological magnetic dynamo. Here we present a novel numerical approach to astrophyiscal MHD simulations aimed to resolve this small-scale dynamo in future cosmological simulations. As a first step, we implement a fifth order WENO scheme in the new code WOMBAT. We show that this scheme doubles the effective resolution of the simulation and is thus less expensive than common second order schemes. WOMBAT uses a novel approach to parallelization and load balancing developed in collaboration with performance engineers at Cray Inc. This will allow us scale simulation to the exaflop regime and achieve kpc resolution in future cosmological simulations of galaxy clusters. Here we demonstrate the excellent scaling properties of the code and argue that resolved simulations of the cosmological small scale dynamo within the whole virial radius are possible in the next years.